Prevention and treatment of the post-thrombotic syndrome. Issue 164 (April 2018) - Pikovsky, Oleg; Rabinovich, Anat
Abstract: Post-thrombotic syndrome (PTS) is a complication that develops in up to 50% of patients with deep vein thrombosis (DVT) and manifests as symptoms and signs of chronic venous insufficiency of varying severity. PTS negatively affects patient's quality of life and causes significant burden to the healthcare system. The risk for PTS development can be markedly reduced by preventing DVT and providing appropriate anticoagulation once it develops. Patients with extensive proximal (iliofemoral) DVT may benefit from invasive interventions, such as catheter-directed thrombolysis. The effectiveness of elastic compression stockings (ECS) for PTS prevention has not been conclusively demonstrated in randomized trials. Treatment of PTS is primarily based on ECS, exercise and lifestyle modifications. The effectiveness of various pharmacologic agents for PTS treatment remains controversial. Surgical or radiological interventions for vein reconstruction or revascularization may be considered in refractory cases. This review summarizes current evidence regarding prevention and treatment of PTS of the lower limbs in adults. Highlights: PTS can be more easily prevented by preventing first or recurrent DVT, than treated. Optimal anticoagulation is essential to reduce the risk and severity of PTS. Patients with iliofemoral DVT may require a more aggressive treatment approach over anticoagulation alone. Treatment of PTS is primarily based on compression therapy. Selected patients with severe PTS can be referred for consideration of interventional procedures in expert centers.